Comparison Between the Facial Flow Lines of Androids and Humans - Ishihara, Hisashi; Iwanaga, Saneyuki; Asada, Minoru (Frontiers in Robotics and AI, 2021)
The behavior of an android robot face is difficult to predict because of the complicated interactions between many and various attributes (size, weight, and shape) of system components. Therefore, the system behavior should be analyzed after these components are assembled to improve their performance. In this study, the three-dimensional displacement distributions for the facial surfaces of two android robots were measured for the analysis. The faces of three adult males were also analyzed for comparison. The visualized displacement distributions indicated two main deformation features in the upper face that potentially characterize the human-likeness while they were not observed in the androids: curved flow lines and surface undulation where the upstream areas of the flow lines elevate. These findings suggest that innovative composite motion mechanisms to control both the flow lines and surface undulations are required to develop advanced androids capable of exhibiting more realistic facial expressions. Our comparative approach between androids and humans will improve androids' impressions in future real-life application scenes, e.g., receptionists in hotels and banks, and clerks in shops.